Educação em saúde na escola pública: limites e possibilidades: uma reflexão histórica sobre a formação do educador - Oliveira, Maria Lucia Cunha Lopes de (1991)
Thinking about schoolteachers' preparation nowadays, the aim is their conscious and criticaI participation in society. Health Education then becomes the object of a theoretical - methodological analysis. This dissertation discusses the failure of the traditional way of teaching Health only as a biological subject and talks about a new approach, Health as a social right. It deals with which considers the relationship between Education, Health and Citizenship in Brazilian society focusing the role of public Elementary Schools in the collective search for health. Considering Education as a mediator practice dialectically articulated to the wider social context, it analyses the possibilities and limitations of Health Education in terms of its contribution towards a better quality of health and living for Brazilian people. The pedagogical trends of Health Education are studied through a historical perspective and its rnain philosophical principIes and ideological contents are identified. The political role of Health Education along the capitalist society forming process 1s also investigated. This dissertation exposes that political comrnitment of educators must be present in their everyday practice. Then the Public Elernentary School will be a forum for the interpretation. and transformation reality. The professional competence is to be collectively under dignified work conditions. of built This situation has to be related to a governrnent educational policy that effectively grants irnportance to the Public Education. Finally it is emphasized the importance of society organization as a t~ay for constitutional rights of Health and Education becorning true for everybody.